Bioengineered Ciprofloxacin-Loaded Chitosan Nanoparticles for the Treatment of Bovine Mastitis - Preeti Yadav; Awadh Bihari Yadav; Preksha Gaur; Vartika Mishra; Zul-I Huma; Neelesh Sharma; Young-Ok Son (Biomedicines, 2022)
Mastitis is the most devastating economic disease in dairy cattle. Mastitis in dairy cattle frequently occurs during the dry period or during early lactation. Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus)are the main causative agents of mastitis in India. S. aureus can form microabscesses in the udder and develop a subclinical form of mastitis. This bacterial property hinders an effective cure during the lactation period. Antimicrobials used for treatments have a short half-life at the site of action because of frequent milking; thereforethey are unable to maintain the desired drug concentration for effective clearance of bacteria. We demonstrated the potential of ciprofloxacin-encapsulated nanocarriersthat can improve the availability of drugs and provide an effective means for mastitis treatment. These drug-loaded nanoparticles show low toxicity and slow clearance from the site of action. Antimicrobial activity against clinical strains of E. coli and S. aureus showed that the zone of inhibition depended on the dose (0.5 mg to 2 mg/mL nanoparticle solution from 11.6 to 14.5 mm and 15 to 18 mm). These nanoparticles showed good antimicrobial activity in broth culture and agar diffusion assay against bacteria.